(untitled) (International Journal of Environmental Sciences, 2025)
The stabilization of problematic soils to enhance their engineering performance, particularly shear strength and bearing capacity, is a critical requirement in geotechnical engineering. In India, expansive soils such as black cotton soil present significant challenges for infrastructure development due to their pronounced swelling, shrinkage, and settlement characteristics, which often lead to structural instability and failure. Traditional soil stabilization techniques, including the use of cement, lime, and industrial by-products like fly ash, although effective, are frequently associated with high costs and environmental concerns. In the present study, an innovative and sustainable approach to soil stabilization is investigated through the incorporation of waste plastic as a soil modifier. This methodology not only addresses the persistent issue of plastic waste management but also offers an eco-friendly and cost-effective solution to improve soil behaviour. A series of laboratory experiments, including particle size distribution (sieve analysis), Modified Proctor compaction tests, and California Bearing Ratio (CBR) tests, were conducted to evaluate the influence of shredded plastic waste on the geotechnical properties of black cotton soil. The sieve analysis provided essential insights into the gradation and physical characteristics of the soil. The Modified Proctor test, which is more suitable for applications requiring high compaction such as subgrade layers in road construction, was employed to determine the Optimum Moisture Content (OMC) and Maximum Dry Density (MDD). The CBR test was utilized to assess the load-bearing capacity of the stabilized soil and to establish the Optimum Plastic Content (OPC)—the percentage of plastic addition beyond which the CBR value starts to decline. The results indicate that the inclusion of plastic waste significantly enhances the load-bearing capacity of the soil up to an optimal dosage, beyond which performance deteriorates. The study confirms that waste plastic can serve as a viable and economical soil stabilizer, contributing to both geotechnical performance enhancement and environmental sustainability. This approach demonstrates considerable potential for application in low-volume roads and embankment construction, providing an effective pathway for the circular utilization of plastic waste in civil engineering practices.